2020
DOI: 10.1021/acsaem.0c00010
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable, Efficient, Vapor Deposited Inorganic Perovskite Solar Cells

Abstract: I would like to dedicate this work to my father, Ashok R. Gaonkar. His dedication, constant support, and tireless enthusiasm made me into the person I am today. He had a zeal for the pursuit of knowledge, which he imparted into me at a very young age. He was incredibly delighted when I decided to pursue a PhD in solar photovoltaics, and I am sure he would be extremely proud of me today. This work is also dedicated to my mother, Shaila Gaonkar, whose strength and love is a continuing source of inspiration to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…There have been plenty of feasible methods to improve the thermal stability of PSCs. For instance, component engineering, additive incorporation, surface passivation, and process optimization are generally employed to improve the heat resistance of perovskite absorbers with substantially improved film quality and effective defect passivation . In addition, with regard to the carrier transport layer employing unstable organic materials, i.e., 2,2′,7,7′-tetrakis­( N , N -di- p -methoxyphenylamine)-9,9′-spirobifluorene (spiro-OMeTAD), which has a poor thermal stability due to its low glass transition temperature, , researchers have found or synthesized a series of more thermally stable alternatives, such as poly­(bis­(4-phenyl)­(2,4,6-trimethylphenyl)-amine) (PTAA), CuSCN, etc., to effectively prolong the lifetime of PSCs under thermal stressors.…”
mentioning
confidence: 99%
“…There have been plenty of feasible methods to improve the thermal stability of PSCs. For instance, component engineering, additive incorporation, surface passivation, and process optimization are generally employed to improve the heat resistance of perovskite absorbers with substantially improved film quality and effective defect passivation . In addition, with regard to the carrier transport layer employing unstable organic materials, i.e., 2,2′,7,7′-tetrakis­( N , N -di- p -methoxyphenylamine)-9,9′-spirobifluorene (spiro-OMeTAD), which has a poor thermal stability due to its low glass transition temperature, , researchers have found or synthesized a series of more thermally stable alternatives, such as poly­(bis­(4-phenyl)­(2,4,6-trimethylphenyl)-amine) (PTAA), CuSCN, etc., to effectively prolong the lifetime of PSCs under thermal stressors.…”
mentioning
confidence: 99%
“…Compared to hybrid perovskites, inorganic perovskites CsPbX 3 (X = Cl, Br, I) show better stability. However, the literature reports that CsPbI 3 is only stable in the suitable perovskite phase at temperatures higher than 300 °C . CsPbI 3 can easily transform rapidly in air to a yellow-colored nonperovskite polymorph that is thermodynamically more stable at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, the literature reports that CsPbI 3 is only stable in the suitable perovskite phase at temperatures higher than 300 °C. 47 CsPbI 3 can easily transform rapidly in air to a yellow-colored nonperovskite polymorph that is thermodynamically more stable at ambient temperature. This perovskite-to-nonperovskite transition is mostly due to the relatively low tolerance factor (0.80) that results in structural instability.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was suggested that the prolonged charge carrier lifetime of vapor‐deposited CsPbI 3 films leads to significant improvement of device efficiency as compared with their spin‐coated counterparts. Gaonkar et al [ 176 ] studied the influence of various important parameters of the perovskite preparation process such as substrate temperatures and precursor layer thickness that regulate the intermixing of the perovskite layer and their influence on the hysteresis and photovoltaic performance of mixed halide CsPbI x Br( 3− x ) perovskite. To prepare the correct stoichiometric perovskite, the precise control of thickness of the individual precursor layers (CsBr and PbI 2 ) is a critical parameter.…”
Section: Dual‐source Evaporation Depositionmentioning
confidence: 99%